Analisis Motif Ornamen pada Kain Tenun Songket Khas Melayu Desa Bandar Khalipah Kecamatan Percut Sei Tuan - M. Aidil Amri; Agus Priyatno (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
Deli Serdang is a district in North Sumatra known for its diversity and significant Malay community commodities. Traditional songket weaving, especially the Deli Tobacco Leaf motif, plays an important role as a symbol of economic growth and prosperity for the Deli Malay community, and is a Malay cultural heritage that must be preserved. This study highlights the Malay songket tradition in Deli Serdang, to reveal its aesthetic and symbolic meaning through interviews with craftsmen and community leaders. The Tobacco Leaf motif, in addition to beautifying the fabric, also reflects traditional artistic values ​​such as balance, proportion, while emphasizing the identity of Indonesian culture. This study encourages the preservation of cultural heritage to remain relevant and modern.